2014
DOI: 10.3892/ijmm.2014.1701
|View full text |Cite
|
Sign up to set email alerts
|

The PI3K/Akt signaling pathway exerts effects on the implantation of mouse embryos by regulating the expression of RhoA

Abstract: The aim of this study was to investigate whether the phosphoinositide 3-kinase (PI3K)/Akt signaling pathway affects the implantation of mouse embryos by regulating the expression of RhoA. The expression of PI3K, Akt, phosphorylated (p-)Akt, phosphatase and tensin homolog (PTEN) and RhoA in the uterus of mice on day 5 of pregnancy (D5) and in pseudopregnant mice was examined by quantitative reverse transcription polymerase chain reaction (qRT-PCR), immunohistochemistry and western blot analysis. A functional an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 32 publications
(51 reference statements)
2
41
1
Order By: Relevance
“…These effects were not dependent on increased cell proliferation (Prast et al 2008). Another set of experiments, performed in mice at 5 days of pregnancy, revealed that implantation sites displayed increased PIK3CA, AKT, and RHOA expression, whereas inter-implantation site displayed increased PTEN expression; AKT was most strongly expressed in the stromal cells and luminal epithelium of the implantation site, while phosphorylated AKT (S473) was strongly expressed in stromal cells of the implantation site (Liu et al 2014). Additionally, the use of contralateral intrauterine injection of LY294002 drastically reduced the number of implanted embryos.…”
Section: Implantationmentioning
confidence: 94%
“…These effects were not dependent on increased cell proliferation (Prast et al 2008). Another set of experiments, performed in mice at 5 days of pregnancy, revealed that implantation sites displayed increased PIK3CA, AKT, and RHOA expression, whereas inter-implantation site displayed increased PTEN expression; AKT was most strongly expressed in the stromal cells and luminal epithelium of the implantation site, while phosphorylated AKT (S473) was strongly expressed in stromal cells of the implantation site (Liu et al 2014). Additionally, the use of contralateral intrauterine injection of LY294002 drastically reduced the number of implanted embryos.…”
Section: Implantationmentioning
confidence: 94%
“…Levonorgestrel is a progestin used for emergency contraceptive and the treatment of menstrual disorders or endometriosis. Among these compounds, it is known that intrauterine injection of LY294002 [59] and sirolimus (rapamycin) [55] decreased the number of implantation sites in mice, demonstrating the validity of our CMap analysis. According to literature, there is high possibility that niclosamide, quinostatin, medrysone, gossypol and levonorgestrel are anti-implantation compounds.…”
Section: Discussionmentioning
confidence: 59%
“…However, 11 upstream regulators were predicted to be activated and two to be inhibited in PR cows. Among them, IGF1 27,53,54 , AGT 52,55 , TNF 56,57 , AKT and PI3K 58,59 , FGF2 20 , TGFβ1 (previously discussed) (activated in PR cows) and NFE2L2 19 (inhibited in PR cows) have been previously associated with endometrial processes and receptivity.…”
Section: Discussionmentioning
confidence: 97%